PENGARUH UNUSUAL MARKET ACTIVITY REPLIES PADA BURSA EFEK INDONESIA TERHADAP REAKSI PASAR SAHAM SELAMA TAHUN 2021 - Rahmat Setiawan; Yohanes Richardo Halim (FEB Universitas Sam Ratulangi Manado, 2023)
This study aims to examine the effect of Unusual Market Activity (UMA) replies on stock market reactions as measured by abnormal returns on the Indonesia Stock Exchange (IDX) in 2021. The sample used in this study was 162 stocks consisting of 14 companies issuing UMA replies with new information and 148 companies that issued UMA replies without new information. Hypothesis testing in this study used the Mann-Whitney U-Test method which was processed using SPSS Statistics. This study concludes that there are significant differences in market reactions (abnormal returns) between companies that issue UMA replies with new information and companies that issue UMA replies without new information. Keywords: abnormal returns; Indonesian stock market; Unusual Market Activity replies; UMA replies